The rise of covenant-lite bond contracting - Gietzmann, M.; Isidro, H.; Raonic, I. (Journal of Accounting, Auditing and Finance, 2023)
We investigate the trading and yield effects of covenant-lite (cov-lite) high-yield bond contracts, which have a restricted (lite) set of covenants. The excluded covenants often are those that use accounting performance measures. Although much research has focused on the potential benefits of accounting as a basis for debt contracting, little is known about settings where it may be optimal to exclude accounting performance statistics from public debt contracts. We find that cov-lite high-yield bonds have a higher trading turnover and lower yield spreads. Our findings provide empirical support for theory, which predicts, for optimal bond covenant design, that a trade-off between improving trading ease versus enhanced investor protection needs to be managed. These results enhance our understanding of the limits of accounting’s role in (bond) contracting design.